Design and Evaluation of a Management Dashboard for a Children\'s Subspecialty Hospital: An Action Research Approach - Malihe Ghanaatjoo; Nader Jahanmehr; Hamed Dehnavi; Aida Samadi (پیاورد سلامت)
Background and Aim: The increase in the amount of information and the need for their daily monitoring have led to the development of tools called management dashboards that have the ability to analyze graphical data. In addition to preparing quick reports in different time frames and user-specific format, the dashboard can be useful for providing dynamic updated information for accurate decision-making and quick response to changes. Materials and Methods: The current research was carried out in the form of qualitative studies and participatory action research method in 9 steps. In this applied and developmental research that was conducted cross-sectionally using the data of the first half of 2022, 11 members of the leadership team of a super-specialized children’s hospital were selected as research participants. The data collection tool was an interview using a questionnaire to determine the importance of indicators and a usability questionnaire (usability) of the dashboard based on three independent variables (usefulness, ease of use and satisfaction). The Excel file of data needed for the dashboard was collected from the HIS system of the hospital, and the dashboard was designed with Power BI software, and the capabilities and access levels of users were determined based on their duties. Data analysis was done using descriptive statistics and Excel software version 2016. Results: In the stage of determining key performance indicators, out of 39 indicators selected by the research team, 22 indicators scored an average score of 4 or higher (from 5 points) and 21 indicators were able to be implemented. The data repository in Excel format was used as an intermediate environment. The dashboard was displayed on six pages (indicators related to the performance of inpatient beds, mortality, emergency and other indicators) and the capabilities of each page were determined. After implementing the dashboard and determining the access levels of users, obtaining a high score from the questions of the usability questionnaire (5 out of 7 points) and obtaining an average score of 71.8 out of 5 questions related to usefulness variables, 70.5 out of 8 questions related to ease of use. And 71 out of 3 questions related to the satisfaction variable showed that the dashboard designed for the hospital had high usability. Conclusion: Hospital management dashboard information can be a basis for informed decision-making to achieve benefits such as identifying the best performance, improving performance quality, making faster decisions, reducing errors, improving capacity management and work flow, allocating resources and planning for growth and development.